2007
DOI: 10.1038/sj.ejcn.1602674
|View full text |Cite
|
Sign up to set email alerts
|

Intake of purple sweet potato beverage affects on serum hepatic biomarker levels of healthy adult men with borderline hepatitis

Abstract: Objective: To examine the effect of purple sweet potato (PSP) beverage rich in acylated anthocyanins on serum hepatic biomarkers in healthy Japanese men. Design: A randomized, double-blind, placebo-controlled, parallel study. Setting: Kumamoto in Japan. Subjects: Healthy adult men (30-60 years) with borderline hepatitis who had one or more of serum g-glutamyl transferase (GGT), aspertate aminotransferase (AST) and alanine aminotransferase (ALT) levels over normal ranges, and who were negative for hepatitis vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(79 citation statements)
references
References 25 publications
2
76
0
1
Order By: Relevance
“…Most of the PSP pigments related studies focused on the neuroprotection [11, 13,16,17], hepatoprotection [12,18,19], immunomodulation [20][21][22], and antiatherosclerosis [23,24]. There has been limited information about the radioprotective effects of PSP pigments.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the PSP pigments related studies focused on the neuroprotection [11, 13,16,17], hepatoprotection [12,18,19], immunomodulation [20][21][22], and antiatherosclerosis [23,24]. There has been limited information about the radioprotective effects of PSP pigments.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that ACNs decrease hepatic lipid accumulation and may counteract oxidative stress and hepatic inflammation in animal studies, but their benefits in patients with NAFLD has not yet been well elucidated [44] . There is only one study evaluating the effects of ACN on NAFLD patients; Suda et al [45] have reported that supplementation with 400 mg of acylated ACNs could reduce levels of liver enzymes, in particular gamma-glutamyl transferases in patients with NAFLD. This clinical trial had many limitations; liver damage was not directly assessed, fatty liver was not confirmed by direct imaging, and the effect of acylated ACNs was not compared to that of a control food or to the lack of intervention [45] .…”
Section: Antioxidants Agentsmentioning
confidence: 99%
“…There is only one study evaluating the effects of ACN on NAFLD patients; Suda et al [45] have reported that supplementation with 400 mg of acylated ACNs could reduce levels of liver enzymes, in particular gamma-glutamyl transferases in patients with NAFLD. This clinical trial had many limitations; liver damage was not directly assessed, fatty liver was not confirmed by direct imaging, and the effect of acylated ACNs was not compared to that of a control food or to the lack of intervention [45] . More research studies are therefore required to evaluate the effects of ACNs supplementation on NAFLD features.…”
Section: Antioxidants Agentsmentioning
confidence: 99%
“…There are several studies, in normal cells and tissues, in which it was demonstrated that anthocyanins, probably involving some protein kinases, modulate the activity of some GSHdependent enzymes, thus ameliorating the antioxidant response (Hou et al, 2010;Suda et al, 2008;Veigas et al, 2008). GSSG formed intracellularly is continuously reduced to GSH by the activity of GR.…”
Section: Gsh Role In Apoptosismentioning
confidence: 99%